Electrical power engineering education down under: Australia and New Zealand are adding energy to their University Curricula - Nair, N.; Martin, D.; Saha, T.; Islam, Syed; Watson, N. (2018)
© 2003-2012 IEEE. On 4 August 1888, Reefton became the first town in New Zealand to have its own public electricity supply powered by hydrogeneration. In Australia, the first supply of electricity to the public at large was in two small country towns in New South Wales. Tamworth, with a population of 3,000, switched on arc and incandescent street lighting on 9 November 1888. In April 1889, the smaller town of Young switched on its incandescent street lighting and shortly thereafter went on to connect shops, offices, and homes within reach of its lines. However, the history of electricity supply in Australia traces back earlier, with Brisbane as one of the first cities in Australia to use electricity commercially, in 1882. Thus, electricity utilization down under coincided with the history of its emergence among the countries of the Northern Hemisphere.